Plasma processes to detect fluorine with ICPMS/MS as [M–F]+: an argument for building a negative mode ICPMS/MS. Issue 8 (15th June 2018) - Azua Jamari, Nor Laili; Behrens, Arne; Raab, Andrea; Krupp, Eva M.; Feldmann, Jörg
Abstract : The paper describes that the 2 nd ionisation potential and the difference in bond energy of a metal to fluorine bond and of a metal to oxygen bond are the most important parameters to form a metal fluoride ion for the detection of fluorine in ICPMS/MS. Abstract : Detection of fluorine with commercial ICPMS is impossible due to the high ionisation potential (IP) of fluorine. A novel approach through the formation of fluorine-containing polyatomic ions [M–F] + in the plasma allows the successful detection of F at sub ppm levels by ICPMS/MS. Two theories behind [M–F] + formation have been proposed, yet there is no clear understanding about the mechanism. Here, different metal solutions were tested for the characterisation of plasma processes in the formation of [M–F] + . Three characteristics: high [M–F] + bond dissociation energy (BDE), low [M–O] + BDE and low IP were found to be essential to get the highest sensitivity for [M–F] + . It was found that for elements with a higher [M–F] + BDE than [M–O] + BDE, the sensitivity decreases linearly with the second IP of the element, meaning that the major process in the plasma is the harvesting of F − by M 2+ to form [M–F] + . Barium exhibited the highest sensitivity for [M–F] + . However, the robustness of this approach was questioned due to matrix effects, hence an argument for re-developing negative ion ICPMS/MS was discussed in which detection limits in the sub-ppb range could be reached.